Advances in computer entertainment : 9th international conference, ACE 2012 Kathmandu, Nepal, November 3-5, 2012, proceedings (Berlin : Springer, 2012)
This book constitutes the refereed conference proceedings of the 9th International Conference on Advances in Computer Entertainment, ACE 2012, held in Kathmandu, Nepal, in November 2012. The 10 full paper and 19 short papers presented together with 5 papers from the special track Arts and Culture and 35 extended abstracts were carefully reviewed and selected from a total of 140 submissions in all categories. The papers cover topics across a wide spectrum of disciplines including computer science, design, arts, sociology, anthropology, psychology, and marketing. Focusing on all areas related to interactive entertainment they aim at stimulating discussion in the development of new and compelling entertainment computing and interactive art concepts and applications